Pengaruh Mutasi Kerja, Beban Kerja dan Konflik Interpersonal terhadap Kinerja Pegawai Kantor Kecamatan Peusangan Kabupaten Bireuen - Maisura, Maisura; Win, Konadi (Singkite Journal, 2023)
This study intends to analyze the performance side of employees at the Peusangan Subdistrict office, Bireuen Regency based on a study of the factors of implementing employee mutations, workload and interpersonal conflicts that occur in the agency. Research begins by demonstrating a problem with quantitative descriptive analysis. Followed by associative analysis between variables with multiple regression analysis model approach. The results of the analysis inform: 1) Descriptively, it shows that the achievement of employee performance is still not optimal, namely .84,22% of expectations. This is in synergy with the findings of the achievement of the imple-mentation of the transfer of new employees 67,07% stated to be beneficial, also from the aspect of new workload 68,36% achievement and the presence of interpersonal conflict resulted in a decrease in performance which was assessed by employees reaching 54,3%. 2) The associative analysis proves that mutations and workload have a positive effect on employee performance, while interpersonal conflict has a negative effect. 3). Simultaneously the factors of job mutation, workload and interpersonal conflict affect employee performance with a contribution of 77.6% and the influence of other factors not involved in the analysis of employee performance is 22.4%.